[Cp*RhCl2]2-catalyzed alkyne hydroamination to 1,2-dihydroquinolines - Kumaran, Elumalai (2015)
[Cp*RhCl2]2 catalyzes the formation of 1,2-dihydroquinolines from the reaction of two terminal alkynes and an aniline. This reaction is believed to proceed via an alkyne hydroamination followed by an alkyne insertion.